Local border traffic as a platform for the development of border cities - Zabielska, Izabela; Zielińska-Szczepkowska, Joanna (International Conference “Environmental Engineering”, 2017)
The paper aims at presenting to answer: Local Border Traffic is a platform for the Development of Border Cities? Cities located in the border zone were subjected to analysis, limiting the study area to the Polish Warmia-Masuria Province and the Kaliningrad Oblast of the Russian Federation. For the needs of the present task, survey studies were designed and carried out, targeting the inhabitants of 13 districts (poviat) of Warmia-Masuria Province (border cities) covered by the Agreement on LBT on the Polish side, as well as respondents residing in the Kaliningrad Oblast on the Russian side, in order to determine the costs and developmental benefits of the Agreement entering into force. Individual interviews represented the basic research method in data collection. The interview questionnaire was the research tool applied. As results from the carried out surveys, Local Border Traffic for border cities: 1) expand economic innovations, 2) the infiltration of social and cultural influences, 3) is a spatial factor of their regional and local development.
Keywords: local border traffic; small cities; border cities; development; the border